Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas VII pada Materi Operasi Bilangan Bulat - Hamapinda, Eryani; Ngaba, Anggriati Ledu; Nuhamara, Yuliana Tamu Ina (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
Problem solving is a measure or knowledge that needs to be mastered in solving problems related to real life. This ability is very important to build new knowledge as well as develop ideas. Therefore, the purpose of this study is to analyze the ability and describe the weaknesses of grade VII students in solving math problems in integer operating materials at SMP Negeri 1 Waingapu. Descriptive research type with qualitative approach. The instruments used were tests, interviews, questionnaires and documentation. The subjects of the study were the wakasek part of the curriculum, mathematics teachers and 7th grade students. The results found that the average math problem solving ability of students based on Polya steps is 59.86 and is in a fairly good category. This is because students do not write down the information encountered, do not analyze the problem first, do not write down the strategies used in solving the problem, lack of basic ability in doing calculations, difficulty in placing the sign of the calculation operation, not used to re-examine the answers that have been done and not used to write conclusions.